Low loss waveguide-based Butler matrix with iris coupling control method for millimeterwave applications - W. Almeshehe, Muataz; Murad, Noor Asniza; A. Rahim, Mohamad Kamal; Ayop, Osman; Zubir, Farid; A. Abd. Aziz, Mohamad Zoinol; N. Osman, Mohamed; Majid, H. A. (Taylor&francis, 2023)
This paper proposes a low loss 4 × 4 Butler matrix based on rectangular waveguide cavity resonators technology for millimeterwave beamforming network using iris coupling method. This method has the advantage of controlling the electricalfields and the couplingfactor inside a complex medium such as waveguide cavity resonators. The coupling factor of 6 dB for 4 × 4 Butler matrix is achieved by tuning the iris coupling k-value between the waveguide cavity resonators. Thus, avoiding a higher phase difference losses and component losses at upper millimeterwave bands. To validate the proposed method, CST software simulations are performed under several iris coupling k-values to achieve a 6 dB coupling factor. Then, the proposed 4 × 4 Butler matrix is 3D metal printed using selective laser melting (SLM) technique. The measured reflection and isolation coefficients are observed below −10 dB, with coupling coefficients ranging between −6 and −7 dB. The phase differences of −42.02°, 42.02°, −130.95°, and 133.3° are achieved at the outputs. It confirmed that using this proposed method has the superiority over the conventional microstrip and waveguide coupling methods by a 1 dB coupling factor loss and a 3° phase difference error.